NON-HOST RESISTANCE ACTIVITIES OF Arabidopsis thaliana INDUCED BY METHANOL EXTRACT OF MYCELIA FROM Phytophthora infestans - Shahjahan Monjil, Mohammad; Wada, Shinya; Takemoto, Daigo; Kawakita, Kazuhito (International Journal of Biosciences and Biotechnology; Vol 1 No 2 (2013))
Defense system of a non-host pathosystem involving the model plant Arabidopsis thaliana and methanolextract of mycelia (MEM) elicitor from Phytophthora infestans are presented in this article. A. thaliana leaveswere analyzed for the induction of reactive oxygen species (ROS), hypersensitive reaction (HR) like celldeath as well as defense gene expression by MEM elicitor. MEM elicitor induced O2¯ generation in A.thaliana leaves with dose dependent nature. HR occurred during the elicitation of A. thaliana challengedwith MEM elicitor. Responses of intact A thaliana seedlings to MEM elicitor caused the retardation of growthof seedlings. Both plant biomass and growth of primary roots was markedly reduced by the treatment ofMEM. MEM elicitor induced the expression of defense genes such as pathogenesis related proteins, PR1,PR2, PR4 and PR5, and rbohF encoding a ROS generation. These results suggested that MEM elicitor inducednon-host defense responses in A. thaliana.
Keywords: methanol extract of mycelia, defense activities, Phytophthora infestans, Arabidopsis thaliana, elicitor